"Waveguidability" of idealized jets. Issue 18 (20th September 2013) - Manola, Iris; Selten, Frank; de, Hylke; Hazeleger, Wilco
<x xml:space="preserve">Abstract</x> [1] It is known that strong zonal jets can act as waveguides for Rossby waves. In this study we use the European Center for Medium‐Range Weather Forecasts (ECMWF) reanalysis data to analyze the connection between jets and zonal waves at timescales beyond 10 days. Moreover, a barotropic model is used to systematically study the ability of idealized jets to trap Rossby wave energy ("waveguidability") as a function of jet strength, jet width, and jet location. In general, strongest waveguidability is found for narrow, fast jets. In addition, when the stationary wave number is integer, a resonant response is found through constructive interference. In Austral summer, the Southern Hemispheric jet is closest to the idealized jets considered and it is for this season that similar jet‐zonal wave relationships are identified in the ECMWF reanalysis data.